2016
DOI: 10.1016/j.ijresmar.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Riding successive product diffusion waves. Building a tsunami via upgrade-rebate programs

Abstract: We discuss how trade-in rebates can be used to manage product multigenerational innovation diffusion waves, and study the optimal behavior of the firm controlling the prices and rebates associated to product upgrades. We show how this strategy accelerates the diffusion and can lead to profit increments of about 5%. The strategy is profitable even when the rebate subsidizes the upgrades entirely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…However, the competition of two generations of products in the market and the threat of the previous generation products to the market share of the next generation products will be alleviated and even disappeared as the time interval extension. First, over time a previous product increases the risk of obsolescence, reducing its competitiveness and impelling new consumers to give up buying the previous product (Avagyan et al, 2016). Newer products usually have the core functionality of previous generations plus some new features (Gunther & Stummer, 2018).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…However, the competition of two generations of products in the market and the threat of the previous generation products to the market share of the next generation products will be alleviated and even disappeared as the time interval extension. First, over time a previous product increases the risk of obsolescence, reducing its competitiveness and impelling new consumers to give up buying the previous product (Avagyan et al, 2016). Newer products usually have the core functionality of previous generations plus some new features (Gunther & Stummer, 2018).…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…For example, Cheng and Cryder (2018) found that consumers may benefit twice from a rebate (double mental discounting): once when they purchase the item and deduct the amount of the rebate from the retail price, and a second time when they actually receive the rebate. Future research may also consider alternative strategies to increase profits through rebates that are applied to bundle purchases (Popkowski Leszczyc & Häubl, 2010;Jeitschko, Jung, & Kim, 2017), or upgrade-rebate strategies used to stimulate sales for new generations of products, such as a new iPhone (Avagyan, Esteban-Bravo, & Vidal-Sanz, 2016).…”
Section: Summary and Implicationsmentioning
confidence: 99%